Reconstruction of large mandibular bone defects extended to the condyle using patient-specific implants based on CAD-CAM technology and 3D printing - Mohamad Bilal Ismail; Khaldoun Darwich (Elsevier, 2022)
Reconstructions of mandibular defects after tumor excision or explosive lesions are one of the most difficult problems facing maxillofacial surgeons, especially when the bony defect includes the mandibular condyle region. Previously, many autogenous or artificial grafts were used to reconstruct these types of defects.As a result of the great development in 3D imaging techniques and virtual surgical planning programs, it became possible to design the bone loss with the mandibular condyle caused by these injuries completely identical to the basic shape of the jaw to ensure the restoration of aesthetic and functional aspects, and then print it using biocompatibility materials through 3D printing techniques.A series of cases in which compensation was made for large mandibular bone defects, including the body of the jaw and the mandibular condyle in one side, resulting from tumor excision, via patient-specific implants (PSI) and 3D printed with titanium material. The aesthetic and functional treatment results were excellent after surgery and without complications. Results: The Patient-specific implants PSI show promising results in reconstructive surgeries for bone defects of the mandible including condyle.